Estimation of the nature and magnitude of mental distress in the population associated with ultra-processed food consumption - Bala, Jerzy; Sukhoi, Oleksii; Newson, Jennifer Jane; Machado, Priscila Pereira; Lawrence, Mark; Thiagarajan, Tara C. (Frontiers in Nutrition, 2025)
IntroductionConvincing evidence supports direct associations between exposure to ultra-processed food (UPF) and risks of depressive and anxiety outcomes. However, the impacts of UPF consumption on broader mental wellbeing and functioning and the aggregate clinical burden of mental distress due to these impacts, are currently unknown. This study probes the relationship between various facets of mental wellbeing and UPF consumption and estimates the magnitude of contribution of UPF to adverse mental wellbeing outcomes.MethodsThis cross-sectional study used data from 400,787 respondents across 60 countries in 2023 who completed a comprehensive assessment of mental functioning, together with a broad range of life context factors including UPF consumption frequency. The relationship between mental wellbeing and UPF consumption frequency was calculated controlling for exercise, traumas & adversities and income. Simulations based on tree-based models (XGboost) to capture nonlinearities and cross-level interactions among 108 factors across 10 categories of life context factors along with SHapley Additive exPlanations (SHAP) values were used to estimate the contribution of UPF consumption to mental wellbeing outcomes.ResultsAltogether, there was a systematic decrease in an aggregate metric of mental wellbeing with increased frequency of UPF consumption (p < 0.001), contributed by increased symptoms of depression as well as challenges with emotional and cognitive control, even when considering major confounds of income, exercise, life adversity and trauma. Simulations based on predictive models that considered over 10 categories of life context factors estimated that 3.4–7.8% of the global sample experienced clinical mental distress linked to UPF consumption, corresponding to a global UPF-associated clinical mental distress burden of 15.3–28.2%, depending on demographic group, with the burden in the United States and Core Anglosphere higher than the global average.DiscussionThis study provides the first quantitative estimate of the aggregate burden of adverse mental functioning associated with increasingly frequent UPF consumption, calling for greater attention to UPF research and policy as a means to mitigate the mental health burden and strengthening the case for incorporating UPF reduction recommendations into national dietary guidelines.